Winter Water Formation in Coastal Polynyas of the Eastern Chukchi Shelf: Pacific and Atlantic Influences. Issue 8 (17th August 2018) - Hirano, Daisuke; Fukamachi, Yasushi; Ohshima, Kay I.; Watanabe, Eiji; Mahoney, Andrew R.; Eicken, Hajo; Itoh, Motoyo; Simizu, Daisuke; Iwamoto, Katsushi; Jones, Joshua; Takatsuka, Toru; Kikuchi, Takashi; et al.
Abstract: Water properties and formation processes of Alaskan Coastal Winter Water (ACWW) over the eastern Chukchi shelf along the Alaska coast, the so‐called Barrow Canyon pathway, are examined using data from moorings, atmospheric reanalysis, satellite‐derived sea‐ice production (SIP), and a numerical tracer experiment. Along this pathway, Pacific Winter Water (PWW) can be modified to produce ACWW through SIP accompanied by production of cold, saline polynya water in the coastal polynyas, upwelling of warm Atlantic Water (AW), and mixing processes on the shelf. Three different types of ACWW are formed: (i) a mixture of AW and PWW, (ii) a mixture of AW and polynya water, and (iii) hypersaline polynya water. The northeasterly winds, correlated with the north‐south atmospheric pressure gradient between Beaufort High and Aleutian Low, are common triggers of polynya SIP episodes and AW upwelling in the Barrow Coastal Polynya (BCP). Due to the dual impact of northeasterly winds, PWW modification processes in the BCP are more complicated than what occurs elsewhere in the Chukchi Polynya. The impact of AW upwelling on the ACWW formation is most prominent in the BCP, usually centered along the coast. All types of ACWW are thought to be basically transported westward or northwestward with the Chukchi slope current and/or Beaufort Gyre and finally contribute to maintenance of the lower halocline layer especially over the Chukchi Borderland, Northwind Ridge, and southern Canada Basin. Even in the Pacific sector of the Arctic Ocean, ACWW properties are strongly influenced by both Atlantic‐origin and Pacific‐origin waters. Key Points: Chukchi polynya winter ice production lacks a trend and is related to interannual fluctuations in northeasterly winds over Barrow Canyon Interannual variability of Alaskan Coastal Winter Water (ACWW) properties is influenced by variability of northeasterly winds Properties of ACWW are strongly influenced by waters of both Pacific and Atlantic origins